Loyalitas Kerja, Efikasi Diri dan Kepuasan Kerja terhadap Keterlibatan Kerja di DPMPTSP Provinsi Jawa Tengah - Muhammad Aulia Rahma Al Mimbar; Mohammad Fauzan (IPM2KPE, 2024)
This research aims to determine the effect of Job Loyalty (X1), Self-Efficacy (X2) and Job Satisfaction (X3) on Job Engagement (Y). The method used in this research is descriptive method and associative method. The research subject used in this research is a scientific target to obtain data with a certain purpose and use about an objective, valid and reliable thing (certain variables). The object of this research is DPMPTSP employees of Central Java Province. Based on the results of research calculations, multiple linear regression analysis. The coefficient of determination (R2) value can be obtained from the variables Job Loyalty (X1), Self-Efficacy (X2) and Job Satisfaction (X3) which influence 91.5% (0.915) on Job Engagement (Y), the remaining 8.5% is influenced by other factors outside this research. In conclusion, work loyalty, self-efficacy and job satisfaction have an impact on work engagement. Keywords: Self-Efficacy, Job Satisfaction, Job Involvement, Job Loyalty